A Pilgrimage of Words. Issue 2 (25th November 2022) - Homrighausen, Jonathan
Abstract : As an artform which interplays word, image, and gesture, calligraphy and lettering arts carry an underrated and understudied potential for exploring sacred texts and theologies. This paper explores that potential through a close analysis of British lettering artist Ann Hechle's 1985 Psalm 121 manuscript. Hechle's manuscript book of this psalm explores relationships between form and content to create a visual performance of the psalm. The product is not merely a beautiful copy of the psalm, but an exegetical engagement with themes of blessing, faith and pilgrimage. Hechle's Psalm 121 visually performs the language of oral blessing, elevates the psalm's affirmation of God's protection, and leads readers on a pilgrimage of hand and eye as they traverse the book's vellum pages. Hechle demonstrates how calligraphy can be so much more than just "beautiful letters."